Tantangan dan peluang dalam menjadi guru profesional - Pradansa, Satria Yudha (Maliki Interdisciplinary Journal, 2024)
Becoming a professional teacher in the modern era presents various significant challenges and opportunities. The main challenges faced include rapid technological developments, the need for student-centered learning, and the demand to continuously update knowledge and skills. Teachers are required to master educational technology in order to increase learning effectiveness and motivate students through innovative and interactive learning methods. Apart from that, they must also be able to manage the diversity of students in the class, both in terms of cultural background, academic ability and special needs. On the other hand, opportunities for professional teachers are also very broad. Technological advances provide various learning resources and tools that make the teaching process easier. Online platforms and social media open access to global learning communities, allowing teachers to share knowledge and best practices with colleagues from around the world. Opportunities for professional development are increasingly diverse, ranging from online courses, workshops, to internationally recognized certification programs. By taking advantage of this opportunity, teachers can continue to improve the quality of themselves and their teaching practices, so as to produce the next generation who are competent and adaptive to changing times. Therefore, becoming a professional teacher not only requires high commitment, but also a willingness to continue learning and adapting.